QARAQALPAQSTANDA EKONOMIKALÍQ HÁM SOCIALLÍQ GEOGRAFIYALÍQ IZERTLEWLER TARIYXÍ HÁM BAǴDARLARÍ - Baltabayev, O.O.; Eshimbetov, U.X.; Atamuratov, I.A. (SCIENCE and SOCIETY, 2025)
The article explores the history and directions of economic and social geographical research in Karakalpakstan. Also, the research work carried out in different directions of economic and social geography in our republic has been subjected to analysis.